RADIKALISME BERAGAMA DALAM TINJAUAN AL-QURAN DAN REALITAS - Nurzen, Kopri (PERADA, 2021)
The world is still preoccupied with issues of radicalism and terrorism. Islam is the religion that is most often the target of accusations of various acts of terrorism and radicalism that occur in the community. Referring to the Al-Quran as its main source, Islam is a religion that is actually far from the shadow of radicalism and terrorism. Islam teaches that there is no compulsion in religion and being religious people comfortably. However, according to the narration conveyed by the Prophet Muhammad, he once prophesied about the existence of a group of people who were appear from His people who were physically good in religion, but his extreme attitude made him able to bounce from religion quickly. Not only Islam, all religious people basically have the same opportunity to be exposed to the disease of religious radicalism.